The genome sequence of the German wasp, Vespula germanica (Fabricius, 1793) [version 1; peer review: 2 approved] - Liam M. Crowley (Wellcome Open Research, 2022)
We present a genome assembly from an individual female Vespula germanica (the German wasp; Arthropoda; Insecta; Hymenoptera; Vespidae). The genome sequence is 206 megabases in span. The majority of the assembly (98.55%) is scaffolded into 25 chromosomal pseudomolecules. The mitochondrial genome was also assembled and is 18.0 kilobases in length. Annotation of the genome assembly on Ensembl has identified 12,361 protein-coding genes.